Chromone and isocoumarin derivatives from the endophytic fungus Xylomelasma sp. Samif07, and their antibacterial and antioxidant activities. Issue 22 (18th November 2021) - Lai, Daowan; Li, Jing; Zhao, Siji; Gu, Gan; Gong, Xiao; Proksch, Peter; Zhou, Ligang
Abstract: Five chromone derivatives, including 2, 6-dimethyl-5-methoxyl-7-hydroxylchromone (1 ), 6-hydroxymethyleugenin (2 ), 6-methoxymethyleugenin (3 ), chaetoquadrin D (4 ), and isoeugenitol (5 ), and three isocoumarin congeners, namely diaporthin (6 ), 8-hydroxy-6-methoxy-3-methylisocoumarin (7 ), and 6-methoxymellein (8 ), were isolated from the culture of the endophytic fungus Xylomelasma sp. Samif07 derived from the medicinal plant Salvia miltiorrhiza Bunge. Among them, compound 1 was a new natural product. Their structures were determined by spectroscopic methods and comparison with the literature. The isolated compounds were evaluated for their antibacterial and antioxidant activities. Compound 5 showed notable antitubercular activity against Mycobacterium tuberculosis with MIC value of 10.31 µg/mL, while compounds 1 –3, and 5 –7 displayed inhibitory activities against the other bacteria with MIC range of 25 ∼ 100 µg/mL. Meanwhile, compound 6 showed potent hydroxyl radical-scavenging activity with EC50 value of 15.1 µg/mL, while compounds 5 –7 showed certain ferric reducing ability. Graphical Abstract: